The wound of mortality : fear, denial, and acceptance of death - Akhtar, Salman, 1946 July 31- (Margaret S. Mahler series., 2010)
Death is a much avoided topic. Literature on mourning exists, but it focuses chiefly upon the death of others. The inevitable psychic impact of one's own mortality is not optimally covered either in this literature on mourning or elsewhere in psychiatry and psychoanalysis. The Wound of Mortality brings together contributions from distinguished psychoanalysts to fill this gap by addressing the issue of death in a comprehensive manner. Among questions the contributors raise and seek to answer are: Dochildren understand the idea of death? How is adolescent bravado related to deeper anxieties abou.